PENGARUH DUKUNGAN SUAMI TERHADAP KETEPATAN KUNJUNGAN ULANG AKSEPTOR KB SUNTIK - Suyati Suyati (Universitas STRADA Indonesia, 2013)
The use of contraception is a shared responsibility of men and women as couples , so that the chosen contraceptive method reflects the needs and desires of the husband and wife . In the use of male contraception , such as condoms and fasektomi , while the husband has the primary responsibility , as a wife when users konrasepsi , the husband can play an important role in supporting his wife and ensure the effective use of contraceptives . Husband and wife should be mutually supportive in the use of contraceptive methods because my family planning and reproductive health is not just a business man or woman saja.Penelitian aims to analyze the influence of husband’s support of the accuracy of repeat visits Kb injectable acceptors.The research method used was a cross sectional analytic study. Respondents in this study is the acceptor Kb injections met the study criteria were 35 people using consecutive sampling technique . The data collected will be processed and analyzed using the Mann – whithney.Hasil statistical tests showed that the majority of the husband to provide enough support for 62.86 % , and most of the acceptor Kb re- injecting a visit Watu is exactly 74.29 % . Based on Mann Whitney test showed a significance of 0.001 , which means there are significant support to the accuracy of repeat visits husband Kb injectable acceptors . The conclusion is there is the influence of husband’s support of the accuracy of repeat visits Kb injectable acceptors.